Affiliate Marketing in Increasing Consumer Interest in Online Shopping: A Sharia Economic Perspective - Hofifah Hofifah; R. Suhaimi (Ta'amul: Journal of Islamic Economics, 2025)
he rapid transformation of e-commerce into a digitally based system has intensified competition among online sellers, requiring innovative marketing strategies to attract consumer interest. One prominent strategy is affiliate marketing, where affiliators promote products through digital platforms and social media. However, the growing use of affiliate marketing raises questions regarding its alignment with Islamic economic principles, particularly in ensuring transparency, fairness, and ethical promotion. This study aims to analyze the role of affiliate marketing in increasing consumer interest in online shopping and to examine its relevance from a Sharia economics perspective. The research employs a qualitative approach using internet searching and library research methods, collecting data from academic journals, scholarly articles, and relevant online references. The findings indicate that affiliate marketing plays a significant role in enhancing consumer interest and influencing purchasing behavior through persuasive promotion, wider market reach, and increased product visibility. From a Sharia economics perspective, affiliate marketing can be considered permissible when it adheres to principles of honesty, transparency, and mutual benefit. This study contributes to the development of Islamic digital marketing literature by providing a conceptual framework that integrates affiliate marketing practices with Sharia economic values, thereby offering guidance for ethical and sustainable online business practices in the contemporary digital economy.